2012
DOI: 10.4236/ajps.2012.37108
|View full text |Cite
|
Sign up to set email alerts
|

Pollen of <i>Bauhinia</i> L. and <i>Phanera</i> Lour. (Leguminosae-Caesalpinioideae) from the Brazilian Caatinga

Abstract: A study of pollen morphology, in species of the genera Bauhinia and Phanera (Leguminosae-Caesalpinioideae) which occur in the Brazilian caatinga, is presented. The pollen was examined using light and scanning electron microscopy. Samples were prepared by the KOH method; non-treated pollen grains were examined by scanning electron microscopy. Pollen grains in Bauhinia species (11) are colpate, but porate in B. cheilantha and B. subclavata. All four species of Phanera present colporate pollen grains; P. outimout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The systematics of living Bauhinia L. is primarily based upon growth habit, inflorescence, flower, calyx, hypanthium, petal, fertile stamen number, stamen filament, gynophore, stigma, pollen, fruit, seed, and leaf morphology [1-8,12,13], as well as molecular data [9,11]. Species of Bauhinia sensu stricto are usually trees or shrubs, rarely semi-scandent plants, whereas those of Lysiphyllum (Benth.)…”
Section: Resultsmentioning
confidence: 99%
“…The systematics of living Bauhinia L. is primarily based upon growth habit, inflorescence, flower, calyx, hypanthium, petal, fertile stamen number, stamen filament, gynophore, stigma, pollen, fruit, seed, and leaf morphology [1-8,12,13], as well as molecular data [9,11]. Species of Bauhinia sensu stricto are usually trees or shrubs, rarely semi-scandent plants, whereas those of Lysiphyllum (Benth.)…”
Section: Resultsmentioning
confidence: 99%
“…The pollen of Bauhinia s. lat. is known to exhibit a great range of morphological features, in terms of ornamentation, apertures, and units of dispersal (dos Santos et al 2012).…”
Section: Proposal To Recognise Phanera Sect Corymbosae As a Distinctmentioning
confidence: 99%
“…In their review for caesalpinioid legumes, Banks and Rudall (2016) associated bat pollination with some degree of pollen supraectal ornamentation, as was also suggested by Dos Santos et al. (2012). Yang et al.…”
Section: Introductionmentioning
confidence: 66%
“…Intraspecific differences in pollen traits are associated with different pollinators (Hasegawa et al, 2023). In their review for caesalpinioid legumes, Banks and Rudall (2016) associated bat pollination with some degree of pollen supraectal ornamentation, as was also suggested by Dos Santos et al (2012). Yang et al (2020) observed a strong relationship between pilate, striate and fossulate ornamentation and bat pollination in lamiids, although they had few samples.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation